Effect of two botanical extracts in the development and content of polyphenol in chili pepper (Capsicum annuum L.) - Tighe Neira, Ricardo; Montalba Navarro René; Leonelli Cantergiani, Gina; Contreras Novoa, Aliro (Revista Mexicana de Ciencias Agrícolas, 2018)
The presence of different types of phytochemicals present in botanical extracts that affect the generation of primary and secondary metabolites (mainly polyphenols) in the cultures in which they are applied, has been considered an important element linked to the beneficial effects of foliar application. The effect of aqueous extract of nettle (Urtica dioica L.) and Ulex europaeus L., on development parameters of chili peppers (Capsicum annuum var longum L. cv. "Cacho de cabra”) as well as on the content of polyphenols in leaf and fruit, such as functional attribute. The trial was conducted under greenhouse conditions in the Araucanía Region, Chile. Extracts were applied in inverse dose N: P ratio 1:3.7 between the passages, each plant completely randomly distributed. The percentage of dry matter (DM %) showed significant differences in the applications of U. europaeus and U. dioica. In fruiting, U. dioica MS % dose 2 had statistically similar in immature fruit than the control and lower than the other treatments. The concentration of polyphenols in leaves and fruits tended to be higher in botanical extracts and significantly lower in the control (p> 0.05) in the final measurement of the production cycle. In fruits U. europaeus presented higher (p≤ 0.05) than the other treatments including the control. These results allow inferring the presence of activator compounds primary and secondary metabolism in plant extracts.